Pelatihan Pemanfataan Botol Bekas Sebagai Media Tanam Hidroponik di Pondok Pesantren Thoriqul Huda - Murniawasih Murniawasih; Mustofa Aji Prayitno; Wirawan Fadly (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The increasing density of the number of students is feared to cause the land around the Islamic boarding school to accumulate garbage and the environment around the Islamic boarding school to become polluted. As a step to overcome these problems, one of the efforts that can be done is by utilizing the waste produced, for example recycling and reusing plastic bottle waste. At this time, plastic bottle waste can be used as a useful medium, one of which is by farming using hydroponic media by utilizing used plastic bottles that are around Islamic boarding schools. The objectives to be achieved in this community service research are 1) to provide skills to the students on how to make hydroponic planting media without using a large area of land; 2) utilize the plastic bottle waste produced into something useful; 3) as an alternative source of food in the form of vegetables for Islamic boarding schools. The method used is the ABCD (Asset Based Community Driven) method which focuses on hydroponic planting using used materials that are around the cottage. The ABCD method is considered appropriate to be applied because it is asset-based which is in line with the potential possessed by Islamic boarding schools. The ABCD method has six stages, namely 1) discovery, 2) dream, 3) design, 4) define, 5) destiny, and 6) reflection. The results of community service research show that with the use of used bottles as hydroponic media, the amount of used plastic bottle waste in Islamic boarding schools can be reduced and it is hoped that it can form a clean and beautiful environment, and the results of hydroponic planting media can be used as an alternative source of energy. food in Islamic boarding schools.